Video analytics : face and facial expression recognition : third International Workshop, FFER 2018, and Second International Workshop, DLPR 2018, Beijing, China, August 20, 2018, Revised selected papers /: face and facial expression recognition : third International Workshop, FFER 2018, and Second International Workshop, DLPR 2018, Beijing, China, August 20, 2018, Revised selected papers. (2019) - Unknown
No abstract available